Investigation of Repurposed Material Utilization for Environmental Protection and Reduction of Overheat Power Losses in PV Panels - Ammar Alkhalidi; Mohamad K. Khawaja; Abdel Ghaffar Al Kelany (International Journal of Photoenergy)
Constant exposure of a photovoltaic (PV) panel to sunlight causes it to overheat and, consequently, its rated efficiency decreases leading to a drop in its generated power. In this study, a PV panel was tested under standard test conditions in a halogen lamp solar simulator at different solar irradiance values. The PV panel was then fitted with heat dissipating fins and measured under identical test parameters; thereafter, repurposed materials such as high-density polyethylene (HDPE) and plastic bags were, separately, added to the PV panel with fitted heat-extraction fins and the performance was evaluated again. Passively cooling the PV panel with fins and repurposed materials resulted in a 22.7% drop in the PV panel’s temperature, while an 11.6% increase in power output occurred at 1000 W m-2. Utilizing repurposed waste materials in PV cooling improves a panel’s efficiency and saves the environment from the ecological effects of dumping these materials.